Past, Present and Future Compensation Research: Economist Perspectives - Michael Gibbs (Institute of Labor Economics (IZA), 2017)
At the 2016 Academy of Management Conference, a group of distinguished compensation researchers held a panel discussion on the future of compensation research. Their remarks were compiled into an article published in this issue. Soon after the panel, Charles Fay commissioned a similar discussion by leading economists (Michael Gibbs, Kevin Hallock, Edward Lazear, Kevin J. Murphy & Canice Prendergast) doing compensation research; this article is the result.
Keywords: J3; M5; 330; compensation; incentives; evaluation; intrinsic motivation